Optimisasi Produksi Refused Derived Fuel Dari Sampah Perkotaan Sebagai Solusi Permasalahan Sampah Di Kota Banda Aceh - Edi Munawar; Zuhra Zuhra; Iqbal Manani; Purnama Arkha (Jurnal Inovasi Ramah Lingkungan, 2020)
There are many methods of waste treatment, but not all methods of waste management can be applied. For example incineration and biogasification require relatively high investment and operational costs, making it less feasiblein developing countries. One of the feasible methods to consider is the utilization of waste as a renewable fuel or commonly referred to as waste derived fuel (RDF). This study aims to determine the composition of municipal waste for RDF production so as to generate optimum fuel value to substitute fossil fuels. The waste used as a sample for RDF production is obtained from TPA Kampung Jawa. Sampling is done twice daily for five consecutive days. Samples are first grouped by type plastic, organic and paper. Subsequently the sample was crushed andsieved into several sizes 2, 6 and 10 mesh. After the preparation process, the samples were analyzed for water content, ash content, elemental content C, H, N, S, O, and fuel value. optimization is done by using Design Expert application. The results of this study showed that organic, plastic and paper waste water content were 34.99 - 54,60 %, 0.42 - 0.64 %, and 2.05 - 3,72 %, respectively. The optimization result with the expert design obtained the optimum composition of RDF is plastic; 29.32 %, paper; 38.99 % and organic; 31.69 %, with the calorificvalue per sample size being 2 mesh 4939,23 kcal/gram), 6 mesh 4939,35 kcal/gram 10 mesh 4939,41 kcal/gram.